Interval-valued fuzzy reasoning method based on similarity measure - Luo, Minxia; Wang, Yajing; Zhao, Ruirui (Journal of logical and algebraic methods in programming, 2020)
In this paper, a new similarity measure of interval-valued fuzzy sets is introduced. Meanwhile, interval-valued fuzzy reasoning method based on similarity measure for Fuzzy Modus Ponens and Fuzzy Modus Tollens are proposed, and the solutions of interval-valued fuzzy reasoning method based on similarity measure are given. Moreover, the robustness of interval-valued fuzzy reasoning method based on similarity measure is discussed. Finally, general interval-valued fuzzy reasoning method based on similarity measure is proposed.